Corrections to “An Opposition-Based Great Wall Construction Metaheuristic Algorithm With Gaussian Mutation for Feature Selection” - Farouq Zitouni; Abdulaziz S. Almazyad; Guojiang Xiong; Ali Wagdy Mohamed; Saad Harous (IEEE Access)
Presents corrections to the paper, An Opposition-Based Great Wall Construction Metaheuristic Algorithm With Gaussian Mutation for Feature Selection.